Workflow complexities of fit criteria on strategy applications and structure adaptations - Hammah, Noriss Kweku; Ibrahim, Rahinah (World Scientific Publishing, 2015)
In studying the correlation between structure–strategy and workflow process, empirical research has shown that knowledge flow has an influence on professional team workflow performance. Using multiple sources of case study evidence, we propose a contingent model of a criteria fit in which the effect of structure on strategies is efficiency of Knowledge Applicability (KA) and effectiveness of Knowledge Adaptability (KA). A case study analysis of building permit approval processing by the Town and Country Planning Department (TCPD) and the various planning agencies in Ghana finds strong support for the model explaining that structure is the measurement attribute determining the efficiency and effectiveness of knowledge flow. A framework of four types of KA is outlined. These show that the viability of organisations is contingent on adaptations of efficient structure and applications of effective strategies. With an emphasis on two organisational environmental variables (uncertainty and equivocality) and structural configuration, we demonstrated the impact of formalisation and centralisation on knowledge flow and workflow process using Virtual Design Team Computational Organisational Theory (VDTCOT).